Australian and South African conicostomatine amphipods (Amphipoda: Lysianassoidea: Lysianassidae: Conicostomatinae subfam. nov.) - Lowry, J. K.; Stoddart, H. E. (Zootaxa, 2012)
The new lysianassid subfamily Conicostomatinae is established. All genera in the subfamily are rediagnosed and distri-bution maps are provided. The new genus Amphorites is established for Amphorites annasona sp. nov., Am. hurleyi (Low-ry & Stoddart, 1983) and Am. pungapunga (Lowry & Stoddart, 1983). The Australian species Conicostoma karta Lowry& Stoddart, 1983 is redescribed with many new distribution records. Three new Australian species are described: Ocosin-go yatala sp. nov.; Scolopostoma darwinensis sp. nov.; and Sc. norah sp. nov. The South African species reported as Stomacontion prionoplax by Griffiths (1974, 1975, 1976) is described as Scolopostoma keurboomstrandensis sp. nov.